Spatial and sociocultural aspects of urban mosque open spaces in Kuala Lumpur, Malaysia: a mixed-method approach - Nizarudin, Norhanis Diyana (Association of Malaysian Environment-Behaviour Researchers (AMER); ABRAmalaysia., 2016)
This paper highlights the application of mixed-method in discovering different perspectives of socio-culture, spatial interactions and behaviours, as well as activities of the multicultural community at selected urban mosque open spaces as part of civic open spaces in Kuala Lumpur, Malaysia. Through systematic observation with behaviour mapping, and focus group discussions, the value of this research lies in representing the urban mosque open spaces as a civic space in enhancing the socio-cultural integration in the society and improving the quality of urban life.